PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 001 SINABOI KECAMATAN SINABOI KABUPATEN ROKAN HILIR - Antosa, Zariul Antosa Zariul; Daud, Damanhuri Daud Damanhur; ', Semi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract :Problem background of this research that student do not understand about IPS lesson. The average score result of IPS test is 56,95. And only 5 of 20 student or 28% in class can reach standard of KKM, while score of KKM is 70. This is the problem: “Do the Inkuiri Learning Model can improve IPS studying result, Student of class IV SD Negeri 001 Sinaboi Kecamatan Sinaboi Kabupaten Rokan Hilir?”. This research form is Observation of Class Action/ Penelitian Tindakan Kelas (PTK). This is the hypothesis of this research: “If the Direct Learning Model is applied therefore gets to increase IPS studying results, Student of class IV SD Negeri 001Sinaboi Kecamatan Sinaboi Kabupaten Rokan Hilir?”. This research is done as much 2 cycles with 6 appointments, there are 4 presentations and 2 times of test. After that, data is collected and analyzed. Test I (UH I) shows the increasing average score, from basic score 56,95 to be 71,9, its increase 14,95 points. And at the Test II (UH II) increase about 8,5 points. So that, the average score is to be 80,4 at the Test II. So, total increasing from basic score to Test II (UH II) is 24,4points. The Classically Completing activity also increase about 25%, basic score percentage 25% at the Test I to be 50%. And at the Test II, percentage score is 80%, its increase 30%. Besides that, activity of teacher and student are increasing in every meeting. Percentage of teacher activity at the first meeting is 66,66%, and at the second is 83,33% (increase 16,67%). Fourth meeting, teacher activity is91,66% (8,3%), and 100% (8,34%) at the fifth meeting. Student activity at the first meeting is 58%, and 70% (12%) at the second meeting. There is increasing to be 87% (17%) at the fourth meeting, and 96% (9%) at the fifth meeting. So, the conclusion is the Implementation of Inkuiri Learning Model can increase IPS studying result, Student of class IV SD Negeri 001Sinaboi Kecamatan Sinaboi. Keywords: Theory, Inkuiri Learning, IPS studying result